Post a New Question

trig

posted by on .

how do i solve this completing the square problem: 3x^2+12x+10=0

  • trig - ,

    3x^2+12x+10=0
    3(x^2+4x+10/3)=0
    (x+2)²-4+10/3=0
    (x+2)²-(√(2/3))²=0
    (x+2+√(2/3))(x+2-√(2/3))=0
    therefore
    x=-2-√(2/3) or -2+√(2/3)

  • trig - ,

    divide by 3

    x^2+4x+10/3=0

    x^2+4x + ???= -10/3 + ???

    well, look at the second term. take one half of it, and square it, add to both sides.

    x^2+4x+4=-10/3+4= 10/3+12/3
    (x+2)^2= 2/3

    take the square root of each side.
    x+2= +-sqrt 2/3
    x=-2+-sqrt 2/3

    check that.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question